Corona Virus- An Overview - N. Aravindha Babu1 , E.P. Sridevi Anjuga2 , N.Anitha3 , L.Malathi3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Coronavirus disease 19 (COVID-19) is a highly communicable and pathogenic viral infection caused bythe severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that has developed in Wuhan, Chinaand spread all over the world.Genomic analysis revealed that SARS-CoV-2 is phylogenetically associatedwith severe, acute respiratory syndrome-like (SARS-like) bat viruses, so bats could be the primary reservoirpossible. The intermediate source of origin and human transfer is unknown, but the accelerated human tohuman transmission has been widely confirmed.Maximal precautionary steps and resources have also beenput forwardby most nations to mitigate transmission and decrease mortality rates.